In cammino dal Forest Fire Area Simulator al nuovo Simulatore FFAS-PLUS a supporto delle attività addestrative di contrasto al Dissesto Idrogeologico - di Fonzo, Marco (GEOmedia, 2023)
In Italy, the repression of forest fires also involves virtual reality, thanks to the Forest Fire Area Simulator (FFAS), a unique technological platform of its kind, with which the “Arma dei Carabinieri” trains soldiers specialized in investigations post forest fire. Realized at the headquarters of the “Scuola Forestale Carabinieri di Castel Volturno”, the system is able to generate immersive and interactive scenarios of forest ecosystems attacked by fire and allows the simulated execution of the technical activities of the judicial police.